The temporal price relationship between the stock index futures and the underlying stock index: evidence from Malaysia - Abdullah, Mahdhir; Mohd Nasir, Annuar; Ramadilli Mohd, Shamsher Mohamad; Ahmed, Huson Joher Ali; Hassan, Taufiq (Universiti Putra Malaysia Press, 2002)
The stock index futures was introduced in Malaysia in December 1995 with the launching of the futures contract on the Kuala Lumpur Stock Exchange Composite Index. Due to its recentness in the country, many issues pertaining to this equity derivatives instrument have not been explored. Thus, the development of stock index futures opens many opportunities for research in this area. This study examines the temporal relationship between the price of the Kuala Lumpur Stock Exchange Composite Index futures contract (FKLI) and its underlying stock index, the Kuala Lumpur Stock Exchange Composite Index (KLSE CI). The five-year period under study is split into three subperiods to observe the price co-movement pattern under different volatility levels. The study finds that futures market tends to lead the spot market by one day during the periods of stable market, and there is a mixed lead-lag relationship between the two markets during the period of highly volatile market.